Peran Kepemimpinan, Soft Competency, dan Iklim Organisasi Terhadap Kinerja Karyawan - Lisna Rita Riama Sinaga; Mukti Rahardjo (Universitas Tarumanagara, 2020)
The purpose of this research is to study the role of leadership, soft competency, and organizational climate on employee performance. This research method uses quantitative descriptive research. This quantitative descriptive research is used to determine the value of independent variables, either one or more variables (independent) without making comparisons, or connecting with other variables. The sample of this study was taken from 82 employee respondents in the company PT. XYZ. Data analysis techniques used in this study are hypotheses and statistical tests, which consist of validity, reliability, classic assessment tests (normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test), and hypothesis testing methods (t test, F test , analysis of the coefficient of determination (R2), analysis of the coefficient of coordination (R)). The results are: (a) There is a positive role in leadership in employee performance; (B) There is a positive role for soft competency in employee performance; (c) There is a positive role for organizational climate in employee performance; (d) The role of leadership, soft competency, and organizational climate has a positive influence on employee performance, which can overcome the variable increase, employee performance is also positive or increased.